2008
DOI: 10.1007/bf02982569
|View full text |Cite
|
Sign up to set email alerts
|

A study of tubular potassium secretory capacity in older patients with hyperkalaemia

Abstract: The inappropriately low baseline TTKG in the OHK group as well as the absence of a response to fludrocortisone indicate tubular insensitivity to aldosterone. GFR values in both OHK (40.06+/-2.31) and ONK (55.58+/-6.1) groups were significantly lower than those in the YNK group (101.66+/-6.9). In aggregate, these findings indicate that older hyperkalaemic patients typically have both impairment of glomerular filtration and renal tubular K+ secretion and highlights the requirement for vigilance in elderly patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The TTKG, used frequently in previous studies [6;1517], was used in this study as a determination of K secretion in the CNT and initial CCD. The accuracy of this approach may be open to question, especially in view of the likelihood of K reabsorption along the collecting ducts (CD).…”
Section: Discussionmentioning
confidence: 99%
“…The TTKG, used frequently in previous studies [6;1517], was used in this study as a determination of K secretion in the CNT and initial CCD. The accuracy of this approach may be open to question, especially in view of the likelihood of K reabsorption along the collecting ducts (CD).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the maximum urinary osmolality decreased by approximately 20% in the 60-79 age group compared to the 20-39 age group (Rowe et al, 1976). At the same time, the ability of aging kidneys to reabsorb sodium and excrete potassium is significantly reduced, leading to a predisposition to water-electrolyte disorders in the elderly (McGreevy et al, 2008;Mimran et al, 1992).…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…[21][22][23] Elderly patients show decreased transtubular potassium gradients and fail to increase distal tubule potassium excretion when hyperkalemic or in response to fludrocortisone. 24 Decreased potassium excretion correlates with decreasing GFR and may reflect a degree of reduced sodium and chloride delivery to the distal convoluted tubule. 25…”
Section: Decreased Tubular Functionmentioning
confidence: 99%